Pippi Longstocking - Lindgren, Astrid Ericsson 1907-; Johnson, Florence Lamborn (New York Scholastic, 1959)
Escapades of Pippi Longstocking, the strongest girl in the world, who lives with a horse and a monkey--but without any parents--in a villa at the edge of a Swedish village.
UCWS-2014-G-1871 donated by Prof. Eric Julian Manalastas.
Keywords: Longstocking, Pippi (Fictitious character) -- Fiction; Humorous stories; Sweden -- Fiction